Research on color optimization of tricolor product considering color harmony and users' emotion. Issue 1 (14th November 2019) - Guo, Fu; Li, Fengxiang; Nagamachi, Mitsuo; Hu, Mingcai; Li, Mingming
Abstract: There are few studies on the tricolor design optimization, and the influence of color‐area ratio on users' emotion has been ignored. This article aims to achieve multiobjective optimization of tricolor product color design. Two modes of color‐area ratio are put forward. Using the proposed method of generating tricolor schemes, 368 tricolor schemes of the representative baby carriage are designed. Through questionnaire survey, color images are screened, and combined with correlation analysis and factor analysis, five perceptual features of color design are determined as "Order, " "Excitement, " "Temperature, " "Color harmony, " and "Users' emotional preference." From two perspectives of color information processing, radial basis function neural networks are used to construct two emotional evaluation models. By integrating the radial basis function neural networks and a genetic algorithm, this study achieves multiobjective optimization of tricolor product color design for two optimization objectives of color harmony and users' emotional preference. Verification results show that the optimization schemes are significantly better than other schemes. Due to similar product characteristics, children's electric car is utilized to verify the generalization capability of the optimization method proposed in this article. It has been demonstrated that the optimization schemes achieve higher scores than randomly selected color schemes and the actual subjective scores match with the predicted scores computed by the color optimization method.